GENERATIVE AI FOR PREDICTIVE CREDIT SCORING AND LENDING DECISIONS INVESTIGATING HOW AI IS REVOLUTIONISING CREDIT RISK ASSESSMENTS AND AUTOMATING LOAN APPROVAL PROCESSES IN BANKING - Archana Todupunuri, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
GenAI is a process that helps in maintaining credit risk assessment and ability for making accurate decisions in loan approval process. Generative AI impacts on the growth of credit risk assessment and automating loan approval processes in the banking sector. Secondary data collection and qualitative strategy have been addressed for developing financial conditions of banking sector. Accumulation of high quality of information can develop outcomes of banking sector to maintain lending decisions and credit risk assessment processes in the banking sector. Data privacy and security can maintain bias in banking sector to develop predictive credit scoring and lending decisions.